2018
DOI: 10.2340/16501977-2490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of respiratory rehabilitation for frail older patients with musculoskeletal disorders: a randomized controlled trial

Abstract: Older persons can be susceptible to respiratory-related conditions, particularly pneumonia. This study examined the effects of breathing training on respiratory function, swallowing function, and quality of life in community-dwelling frail older persons with musculoskeletal disorders. The participants were divided into 2 groups. One group performed a regular rehabilitation programme, and the other group performed breathing training exercises, including a coughing exercise, respiratory muscle stretching exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 11 publications
(12 reference statements)
1
44
0
Order By: Relevance
“…However, exercise training is the core of respiratory rehabilitation, its effect is affected by the way, intensity, time and place of exercise training, and reasonable exercise training has a positive impact on the physical and mental health and QoL of COVID-19 patients [10]. Maki [11] et al evaluated a study of 2504 patients with chronic obstructive non-disease who received exercise intervention and found that the patients' muscle strength increased by 78%, muscle endurance increased by 92% and muscle mass increased by 88%. The mechanism of action of exercise training on COPD rehabilitation is mostly related to the improvement of ventilation and gas exchange function, cardiovascular function and limb muscle function in patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exercise training is the core of respiratory rehabilitation, its effect is affected by the way, intensity, time and place of exercise training, and reasonable exercise training has a positive impact on the physical and mental health and QoL of COVID-19 patients [10]. Maki [11] et al evaluated a study of 2504 patients with chronic obstructive non-disease who received exercise intervention and found that the patients' muscle strength increased by 78%, muscle endurance increased by 92% and muscle mass increased by 88%. The mechanism of action of exercise training on COPD rehabilitation is mostly related to the improvement of ventilation and gas exchange function, cardiovascular function and limb muscle function in patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rehabilitation can improve respiratory function and QoL in patients with chronic obstructive pulmonary disease (COPD) [5]. However, the effect of respiratory rehabilitation on respiratory function and QoL in older adults with COVID-19 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria included the following: history of stroke diagnosed by clinicians and needing rehabilitation, more than 65 years of age, 6 months since acute disease onset, and period since stroke onset of >6 months, and being in a physical condition that can be described as “frail” as defined by the Fried Frailty Criteria (Cardiovascular Health Study: CHS index) 13 . Participants who could not use an auto spirometer or with moderate or severe cardiac disease (New York Heart Association 14 Classification of III or IV) 7,15 were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…For the intervention group, each 20‐min rehabilitation session was held once a day and was made up of 10 mins of pulmonary training in addition to 10 min of standard rehabilitation 7,15 . The pulmonary training intervention comprised the following: pulmonary muscle training, stretching exercise, and home exercise 7,15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…In prevention cardiovascular disease (15) and coronary heart disease (16) and the management of hypertension (17). It also improves the respiratory function and QoL in patients with chronic obstructive pulmonary disease (COPD) (18). However, the effect of respiratory rehabilitation in COVID-19 is unknown here an attempt is being made to explain the use and effect of pranayama in mild to moderate condition & rehabilitation in discharge patients of current pandemic situation COVID -19by considering the physiological changes by the practice of Pranayama.…”
Section: Introductionmentioning
confidence: 99%